Hipertiroid dan Badai Tiroid: Tinjauan Pustaka - Nina Yolanda Putri; Ariadi Humardhani; Kusmardi, Kusmardi (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Hyperthyroidism is an endocrine disorder characterized by excessive production of thyroid hormones, with Graves' disease being the most common cause. This condition can lead to serious complications, including thyroid crisis or storm, which is a medical emergency with a high mortality risk. This article aims to review the literature related to the definition, epidemiology, etiology, clinical manifestations, pathophysiology, diagnosis, management, complications, and prognosis of hyperthyroidism and thyroid crisis. The writing method used a narrative literature review based on national and international literature from 2014 to 2024 obtained through PubMed, ScienceDirect, Google Scholar, and Sinta-indexed national journals. The results of the review show that hyperthyroidism has a broad impact on organ systems, with cardiovascular and metabolic complications being the main burden. Thyroid crisis, although rare, remains a serious threat that requires prompt, aggressive, and multidisciplinary management. In conclusion, early detection, accurate diagnosis, and guideline-based therapy are key to improving patient prognosis and reducing mortality.